Improved Constraints on the Vertical Profile of CH4 at Jupiter’s Mid- to High Latitudes, Using IRTF-TEXES and SOFIA-EXES Spectroscopy - James A. Sinclair; Thomas K. Greathouse; Rohini S. Giles; Matthew Richter; Maisie Rashman; Curtis de Witt; Julianne Moses; Vincent Hue; Pablo Rodríguez-Ovalle; Thierry Fouchet; Ananyo Bhattacharya; Bilal Benmahi; et al. (The Planetary Science Journal)
We present radiative transfer analyses of IRTF-TEXES and SOFIA-EXES mid-infrared spectra of Jupiter's mid- to high latitudes recorded between 2019 April 16 and 2023 July 20. The spectra were inverted across a photochemical model grid of varying eddy diffusion coefficient profiles, and the quality of fit of the synthetic spectra to the observed was used to constrain the CH _4 homopause level. For a subset of latitudes/dates, we find that the CH _4 homopause level is elevated in the region enclosed inside of, or magnetospherically poleward of, the northern ultraviolet main auroral emissions (MAEs) in comparison to the region outside or equatorward of the MAE. For example, using SOFIA-EXES results on 2021 June 10, we derived a CH _4 homopause level of log( p _H (nbar)) = 1.54 ${}_{-0.69}^{+0.51}$ or z _H = 453 ${}_{-76}^{+128}$ km above 1 bar poleward of the northern MAE at 68 ^∘ N compared to a lower limit of log( p _H ) > 2.43 and upper limit of z _H  < 322 km derived equatorward of the northern MAE. We therefore conclude that the region poleward of the northern MAE is, at times, subject to enhanced vertical transport resulting from auroral energy deposition. The exact mechanisms responsible for the enhanced vertical transport in Jupiter's auroral regions are uncertain: time-dependent circulation modeling of Jupiter's polar atmosphere is required to better understand this phenomenon. Poleward of the southern MAE, derived homopause levels agreed within uncertainty with those at equatorward locations. However, we consider this result a spatial sampling artifact rather than concluding that the southern auroral region is not subject to enhanced vertical transport.